GPR and ERT explorations at the archaeological site of Kılıç village (Isparta, SW Turkey) - Yilmaz, Sedat; Balkaya, Çağlayan; Çakmak, Olcay; Oksum, Erdinc (Journal of applied geophysics, 2019)
An archaeo-geophysical survey was conducted through ground-penetrating radar (GPR) and electrical resistivity tomography (ERT) techniques at the archaeological site of Kılıç village located 45 km from the cities of Isparta and Burdur in the Lakes Region of SW Turkey. In the exploration, a GPR reflection profiling survey was primarily conducted over 72 profiles 0.5 m apart using a 500 MHz shielded antenna in the S-N direction. The presence of three-aisled basilica displaying a central nave with an aisle on each side and an apse at the end was successfully revealed. Based on the GPR results, the width of the inner and outer walls of the basilica are about 3 and 1.7 m, respectively. An ERT survey was then carried out via Wenner-Schlumberger array on 37 parallel profiles 1 m apart in NW–SE direction. Depth slices obtained from both two- and three-dimensional inversions of apparent resistivity data were considered in the evaluation. The ERT findings displaying the main structure of the basilica support the results of the GPR survey. Since Kılıç village may be a part of the ancient Baris town according to some views, these findings together with the previous one obtained from about 100 m from the present area may indicate new assessments on the subject. Therefore, we strongly suggest a more detailed archaeological investigation in the village by considering the risk of damage due to illegal excavations. •An archaeo-geophysical survey through GPR and ERT techniques in Kılıç Ören site•The survey mapped a structure similar to a basilica.•It displays a central nave with an aisle on each side and an apse at the end.•A simplified schematic plan of the basilica is presented.•An illegal excavation in the survey area supports obtained results.